THE USE OF STYLISTIC DEVICES IN ENGLISH PROVERBS: IRONY, ANTITHESIS, AND PARADOX - Allamurodova Shaxnozabonu Umidulloyevna; Khudoyberdieva Oyjamol Muzaffarovna (International Journal of Literature and Language Studies, 2026)
This study explores the linguistic, semantic, and cognitive mechanisms of irony, antithesis, and paradox in English paremiology. Although phonetic devices such as rhyme, rhythm, and alliteration contribute to the memorability of proverbs, semantic stylistic devices play a more significant role in shaping their philosophical and communicative meaning. The findings reveal that antithesis, irony, and paradox are not merely decorative features, but important stylistic mechanisms that help proverbs express cultural wisdom, moral judgment, and practical experience in a concise form.